Type 1 diabetes mellitus and oral health: assessment of coronal and root caries - Moore PA, Weyant RJ, Etzel KR, Guggenheimer J, Mongelluzzo MB, Myers DE, (Blackwell Synergy, 2001)
The oral health of a large cohort of adult insulin-dependent diabetic patients (Type 1), diagnosed 24 years previously with juvenile onset, was comprehensively assessed.